2019
DOI: 10.1590/0103-6440201902533
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Abutment Collar Height and Implant Length on Stress Distribution in Single Crowns

Abstract: This in silico study evaluated the influence of the abutment collar height and implants length on the biomechanical behavior of morse taper single dental implants with different crown-to-implant ratio. Six virtual models were constructed (S11, M11, L11, S13, M13 and L13) by combining short (S: 2.5 mm), medium (M: 3.5 mm) or long (L: 4.5 mm) abutment collar heights with different implant lengths (11 or 13-mm). An upper central incisor of 11-mm height was constructed on top of each abutment. Each set was positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
2
10
0
3
Order By: Relevance
“…Among the main findings of our study, we can mention the differences found regarding the dimensions of the abutments used. As noted by other studies, abutment height is a key factor for the behavior and protection of the marginal bone of the implants [ 56 , 57 , 58 ]. These studies reported a higher marginal bone remodeling for abutments <2 mm compared to those ≥2 mm, corroborating the results obtained in the present study, which found statistically significant rMBL between the 2.5 and 3.5 mm in comparison to the abutment of 1.5 mm in transmucosal height.…”
Section: Discussionmentioning
confidence: 95%
“…Among the main findings of our study, we can mention the differences found regarding the dimensions of the abutments used. As noted by other studies, abutment height is a key factor for the behavior and protection of the marginal bone of the implants [ 56 , 57 , 58 ]. These studies reported a higher marginal bone remodeling for abutments <2 mm compared to those ≥2 mm, corroborating the results obtained in the present study, which found statistically significant rMBL between the 2.5 and 3.5 mm in comparison to the abutment of 1.5 mm in transmucosal height.…”
Section: Discussionmentioning
confidence: 95%
“…Some angled abutments have been also recommended to correct a misplaced implant and improve the prosthetic treatment (Cavallaro & Greentein, 2011). However, when implants are placed shallower than ideal position, the restoration can be esthetically affected by angled abutments (Bordin et al, 2019) and the UCLA abutment can be a viable option (Goiato et al, 2015).…”
Section: Fmentioning
confidence: 99%
“…A diferença das alturas de transmucoso como consequência do posicionamento do implante na crista óssea pode apresentar certa influência na distribuição de tensões para o osso periimplantar. Em um estudo conduzido por Bordin et al (2019), os autores avaliaram a influência da altura do transmucoso na distribuição de tensões para o osso periimplantar e os resultados mostraram que o aumento do transmucoso gerou uma maior concentração de tensões em osso cortical, concluindo que a utilização de uma maior altura de transmucoso provocaria um aumento da relação coroa/implante e, em consequência, uma maior altura do transmucoso aumenta o efeito de alavanca Assim, no presente estudo os níveis de tensão, em termos de valores máximos e de área submetida a tensão, no osso peri-implantar, tanto para os modelos A-1.5 e B-1.5 como para os modelos A-3.0 e B-3.0 são influenciados pelo diâmetro da base de assentamento protético, onde um maior diâmetro de assentamento protético (B-1.5 e B-3.0) provocou uma diminuição da tensão ao osso peri-implantar de 3.9 % em média para o carregamento oblíquo. Ainda, quanto à altura do transmucoso, para os modelos A-3.0 e B-3.0, a utilização de um pilar com maior diâmetro em base de assentamento protético parece ter uma maior influência sobre a tensão peri-implantar diminuindo as tensões transmitidas para osso periimplantar.…”
Section: )unclassified
“…acordo com estudo conduzido porBorie et al (2018), em que foi avaliada a influência da distribuição de tensões na interface implante/pilar e implante/osso, os autores concluíram que à medida em que há aumento de altura do transmucoso, maiores tensões são geradas no próprio transmucoso do pilar protético, concordando com estudo recente desenvolvido porBordin et al (2019).Para o presente estudo, a utilização de pilar protético com maior diâmetro de base de assentamento protético (modelos B-1.5 e B-3.0) provocou uma diminuição de tensões tanto para o posicionamento do implante ao nível cristal (B-1.5) como para a colocação subcristal (B-3.0). Esses resultados coincidem com os achados deAbraham et al (2016), onde a utilização de pilares protéticos de maior diâmetro promoveu melhor distribuição de tensões, quando comparado com um pilar com menor base de assentamento protético.…”
unclassified